Applying the Theory of Planned Behavior to Cyberloafing: Drivers and Performance Consequences in an Indonesia’s Cement Company - Yulihasri Yulihasri; Hendra Lukito; Andra Septian; Idris Gautama So; Andrianirina Lanto Nambinintsoa (Binus Business Review, 2026)
The research investigated how the Theory of Planned Behavior (TPB) factors, attitudes, subjective norms, and perceived behavioral control influenced cyberloafing among employees at PT XYZ, and how such behavior subsequently related to employee performance. While prior literature often assumed that cyberloafing reduced productivity, the research challenged that perspective by examining its potential as a form of workplace microbreak. Data were collected from 126 employees using a structured questionnaire on a five-point Likert scale and analyzed through Structural Equation Modeling (SEM) with SmartPLS 4.0. The findings reveal three main results. First, all TPB constructs significantly predict higher levels of cyberloafing, underscoring the role of psychological and social factors in shaping Internet use at work. Second, patterns of cyberloafing differ across organizational roles, with administrators engaging more frequently than operators. Third, contrary to conventional assumptions, cyberloafing shows no significant negative effect on overall work performance. These results suggest that, in this industrial context, limited cyberloafing may operate as a mechanism for stress relief and concentration recovery rather than as a drain on productivity. By providing empirical evidence from an Indonesian state-owned enterprise, the researchers contribute to a more nuanced understanding of cyberloafing, highlighting its cultural and organizational dimensions and questioning its universally negative portrayal.